Cardiovascular Considerations in Patients with Liver Cirrhosis - Vogt, Braden; Chu, Antony F. (Digestive Disease Interventions, 2022)
Liver cirrhosis is a significant cause of morbidity and mortality and can result in alterations to cardiac function. Patients with cirrhosis may develop a hyperdynamic circulation. Furthermore, systolic or diastolic function may occur, although diastolic function is more common. The transjugular intraheptic portosystemic shunt (TIPS) is an increasingly prominent procedure to treat portal hypertension that can result in transient worsening of hyperdynamic circulation. TIPS can be complicated by cardiac decompensation, with diastolic dysfunction playing a key role. Investigators developed an algorithm to stratify risk of cardiac decompensation after TIPS using natriuretic peptide levels and echocardiography. Eighty percent of patients with aortic stenosis decompensated after TIPS in one cohort, but this requires further study before it is considered a contraindication. Cirrhosis has also been linked to development of atrial fibrillation, although data remain mixed. The first-choice anticoagulant should be direct oral anticoagulants, as studies show superior outcomes to warfarin. QTc prolongation is often seen in patients with cirrhosis, theoretically predisposing to ventricular arrhythmias, however the clinical significance remains unclear. The impact of TIPS on arrhythmia is understudied, but small cohorts found high rates. Overall, cirrhosis can have significant impacts of cardiac function and clinicians must be aware of these alterations.
Keywords: cirrhosis; arrhythmia; TIPS; cirrhotic cardiomyopathy; hemodynamics